2018
DOI: 10.1680/jgele.17.00180
|View full text |Cite
|
Sign up to set email alerts
|

Effects of biochar on water retention and matric suction of vegetated soil

Abstract: Biochar is the pyrolysed biomass which has been used as a soil amendment to improve plant performance. This study aims to investigate the effects of biochar–plant interaction on soil water retention and matric suction in silty sand (SM). In total, four soil conditions, namely soil with and without tree (Schefflera heptaphylla), biochar-amended soil (BAS) with and without tree, were subjected to drying. Three replicates were considered for each vegetated soil. By adding 10% (v/v) of biochar, the optimum water c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(19 citation statements)
references
References 37 publications
4
14
0
Order By: Relevance
“…The saturated water content of BAS was 15% higher than NS (refer to Table 3). A similar trend was found in previous experimental reports (Garg et al, 2019; Ni, Chen, Ng, & Guo, 2018), even though the results obtained in this study are slightly higher than previous findings. The higher values in this study may be due to the embedded effect caused by the particle size distribution of clay (Wong, Chen, Chen, Ng, & Wong, 2017) and the different types of biochar.…”
Section: Discussionsupporting
confidence: 92%
“…The saturated water content of BAS was 15% higher than NS (refer to Table 3). A similar trend was found in previous experimental reports (Garg et al, 2019; Ni, Chen, Ng, & Guo, 2018), even though the results obtained in this study are slightly higher than previous findings. The higher values in this study may be due to the embedded effect caused by the particle size distribution of clay (Wong, Chen, Chen, Ng, & Wong, 2017) and the different types of biochar.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, the presence of water-absorbing surface functional groups or bond in biochar holds the water inside of these pores especially in intrapores, i.e., the pores provide only spaces for storage and the functional group holds water in it. The trend of increased water retention in biochar-amended soil was reported by the previous researchers (Bordoloi et al 2018b;Ni et al 2018).…”
Section: Effect Of Biochar On Swrcsupporting
confidence: 78%
“…Previous studies reported that the amendment of biochar in soil increased the Atterberg limits and the optimum moisture content (OMC) and decreased the maximum dry density (MDD) (Yaghoubi and Reddy 2011;Ni et al 2018;Williams et al 2018). It was also found that the saturated hydraulic conductivity decreased in sandy soil while increased in clayey soil when biochar was amended (Uzoma et al 2011;Igalavithana et al 2017;Wong et al 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, biochar can promote feeding root development, which is consistent with our observation. The reduced diameter of roots can be explained by more root occupancy of soil pore space [63]. The largest root length and the highest number of root tips, forks, and crossings were found at 15% biochar amendment.…”
Section: Evaluation Of Root Architecturementioning
confidence: 97%